2018
DOI: 10.1111/jdi.12869
|View full text |Cite
|
Sign up to set email alerts
|

Soluble CD163 correlates with lipid metabolic adaptations in type 1 diabetes patients during ketoacidosis

Abstract: Introduction: Diabetic ketoacidosis (DKA) is associated with inflammation and increased lipolysis. The macrophage activation marker, soluble CD163 (sCD163), is associated with obesity, non-alcoholic fatty liver disease and type 2 diabetes. We aimed to investigate whether sCD163 correlates with key elements of lipolysis in type 1 diabetes patients during mild DKA. Materials and Methods: We investigated nine patients with type 1 diabetes twice during: (i) euglycemic control conditions and a bolus of saline; and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…In agreement with previous studies [1,2], the current study found that sCD163 independently predicted central obesity, MetS, and NAFLD. In addition, the finding of the study further strengthened the importance of a healthy dietary pattern in preventing diet-related chronic disease such as elevated sCD163 levels and MetS.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with previous studies [1,2], the current study found that sCD163 independently predicted central obesity, MetS, and NAFLD. In addition, the finding of the study further strengthened the importance of a healthy dietary pattern in preventing diet-related chronic disease such as elevated sCD163 levels and MetS.…”
Section: Discussionsupporting
confidence: 93%
“…Substantial evidence has demonstrated a positive relationship between circulating soluble cluster of differentiation 163 (sCD163) concentrations and obesity-related comorbidities such as diabetes, non-alcoholic fatty liver disease (NAFLD), and metabolic syndrome (MetS) [1,2]. CD163 is a transmembrane scavenger receptor mainly expressed on monocyte-macrophage cell lineages.…”
Section: Introductionmentioning
confidence: 99%
“…sCD163 is a marker of macrophage activation [ 65 ] and it has been associated with a number of inflammatory diseases such as atherosclerosis [ 80 , 81 ], hemophagocytic lymphohistiocytosis [ 82 , 83 , 84 ] and diabetes mellitus [ 85 , 86 ] including diabetic polyneuropathy [ 87 ], diabetic ketoacidosis [ 88 ] and proliferative diabetic retinopathy [ 89 , 90 ]. Further, a recent paper reviewed sCD163 as a potential biomarker of acute and chronic liver disease and found it elevated in relation to severity in multiple studies [ 91 ].…”
Section: The Cd163 + Macrophagesmentioning
confidence: 99%
“…CD163, a hemoglobin-haptoglobin scavenger receptor, is exclusively expressed by monocytes and macrophages ( 23 , 24 ) and exerts its main biological function through elimination of hemoglobin-haptoglobin complexes during hemolysis ( 25 ). A soluble form (sCD163) is present in the plasma ( 26 ), and enzymatic receptor cleavage of CD163 by the TACE/ADAM17 system is highly upregulated in response to inflammatory stimuli, including the PAMP lipopolysaccharide (LPS) ( 27 30 ). The mannose receptor is primarily expressed by macrophages, dendritic cells and endothelial cells ( 31 ) and is involved in scavenging events including endogenous molecule clearance besides antigen presentation ( 32 ).…”
Section: Macrophage Activation Markersmentioning
confidence: 99%